Glycosylated hemoglobin level may predict the severity of gastroparesis in diabetic patients. (January 2018) - Izzy, Manhal; Lee, Mindy; Johns-Keating, Krysta; Kargoli, Faraj; Beckoff, Steven; Chun, Kwang; Tokayer, Aaron
Highlights: Higher glycated hemoglobin level is associated with slower gastric motility. Higher glycated hemoglobin level can be associated with worse gastroparetic symptoms. Intensive glycemic control might prevent or improve diabetic gastroparesis. Abstract: Aim: To investigate the association between glycemic control represented by glycated hemoglobin (HbA1c) level and the value of 4-h gastric retention on nuclear scan. Methods: We retrospectively reviewed records of diabetic patients who had 4-h nuclear gastric emptying study, with documented 4-h retention value, between January 1st, 2002 and July 30th, 2014 and had HbA1C level close to the time of the study. We divided our cohort into patients with good glycemic control (HbA1C <7, group A), fair control (7–9, group B), and poor control (>9, group C). The 4-h retention value and symptoms were compared between the 3 groups. Results: Our cohort included 299 patients; mean age was 59 ± 14. The median interval between performing gastric emptying study and measuring HbA1C was 41 days. There were 94 patients in group A (HbA1C 6.1 ± 0.4), 131 patients in group B (HbA1C 7.9 ± 0.5), and 74 patients in group C (HbA1C 10.9 ± 1.6). The mean gastric retention value was different between the three study groups, 8.3% ±17, 11.5% ±19, and 14.4% ±21, respectively (P = .03). Conclusion: This is the first study to show that HbA1C level is significantly associated with the 4-h retention value on nuclear gastric emptying scan.